Chernobyl seed project. Advances in the identification of differentially abundant proteins in a radio-contaminated environment - Rashydov, Namik M.; Hajduch, Martin (Frontiers in Plant Science, 2015)
Plants have the ability to grow and successfully reproduce in radio-contaminated environments, which has been highlighted by nuclear accidents at Chernobyl (1986) and Fukushima (2011). The main aim of this article is to summarize the advances of the Chernobyl seed project which has the purpose to provide proteomic characterization of plants grown in the Chernobyl area. We present a summary of comparative proteomic studies on soybean and flax seeds harvested from radio-contaminated Chernobyl areas during two successive generations. Using experimental design developed for radio-contaminated areas, altered abundances of glycine betaine, seed storage proteins, and proteins associated with carbon assimilation into fatty acids were detected. Similar studies in Fukushima radio-contaminated areas might complement these data. The results from these Chernobyl experiments can be viewed in a user-friendly format at a dedicated web-based database freely available at www.chernobylproteomics.sav.sk.